ETIKA PENYIARAN DALAM PERSPEKTIF ISLAM - Abdul Rachman (Jurnal Dakwah Risalah, 2013)
From the point of view of broadcasters as media, Malvin L. DeFleur & Everet E. Dennis, Understanding Mass Communication, which is a type of media that uses electromagnetic instrument in conveying the message to the audience simultaneously. While broadcasting is called broadcasting has the meaning as: "pemancarluasan activities by means of transmitting broadcast and / or transmission facilities on land, at sea or in space by using the radio frequency spectrum (radio signals) in the form of waves. Ethics comes from the Greek word is "Ethos". In the singular, "ethos" means ordinary residence, pastures, stables, habits, customs, morals, feelings, ways of thinking. In terms of philosophy, ethics means of the usual science or knowledge about customs. In Indonesian dictionary is the science of the principles of morals. as proselytizing religions require people to internalize, transmission, diffusion, transformation, and the actualization of the Shari'ah and media methods that originates in the al-Qur’an, as the book of preaching, and the sunnah of the Prophet to mad'u (mankind). This is a Muslim initiative to make syaria'at Islam became a reality in the lives of individuals, families, communities and audiences realized in congregation so that Bohemian ummah good good good in the world now and in the hereafter. So together we have seen the publication of ethics and syari turns "at Islam should have a strong relationship so that it will give impetus to the development and prosperity of society and the nation. Until not so easy Indonesian society teracuni by bad news on the controversial ruling.